2022
DOI: 10.5455/njppp.2023.13.084062022010102022
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of emergency contraceptive pills among female patients of family planning unit of tertiary care teaching hospital, Rajkot, Gujarat, India

Abstract: Background: In India, sizeable population of pregnancies are either unplanned or unwanted and thus these pregnancies add to the population burden or the women may resort to pregnancy termination by traditional or harmful methods leading to serious health consequences. Emergency contraception, developed from trials and research during the past 10 years with aim to cut down the occurrence of unwanted and unintended pregnancies and abortion is one most important step being taken to solve the problem. Aims and O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…For example, alike our results, a study reported a high level of EC awareness among urban population. Nevertheless, opposing results were reported by past researchers (21) i.e., lesser awareness level among rural populations. These discrepancies highlight the influence of socioeconomic factors and geographic location on EC awareness.…”
Section: Discussioncontrasting
confidence: 58%
“…For example, alike our results, a study reported a high level of EC awareness among urban population. Nevertheless, opposing results were reported by past researchers (21) i.e., lesser awareness level among rural populations. These discrepancies highlight the influence of socioeconomic factors and geographic location on EC awareness.…”
Section: Discussioncontrasting
confidence: 58%
“…In comparison, 24.8% went for IUDs, and only 19.2% selected OCPs as their preferred mode of contraception whereas 3.2% said that they would go for the withdrawal method. This was in stark difference to a study done among medical students in a tertiary care center of coastal Karnataka where 91% of students chose condoms whereas, 4% of students went for IUDs and OCPs each and only 1% of students selected coitus interruptus as their choice of contraception [26].…”
Section: Mehta and Dudhiacontrasting
confidence: 67%